2012
DOI: 10.1108/17561391211262175
|View full text |Cite
|
Sign up to set email alerts
|

The influences of entrepreneurial orientation on product advantage and new product success

Abstract: PurposeThe purpose of this paper is to improve understanding of what makes or breaks a new product by exploring the direct and indirect impacts of the three dimensions of entrepreneurial orientation (EO) – innovativeness, risk taking and proactiveness – on product advantage and new product success (NPS).Design/methodology/approachBased on the literature reviewed, theoretical relationships among five constructs and relevant hypotheses were developed and subsequently tested using data collected from 244 electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 91 publications
0
13
0
1
Order By: Relevance
“…The other predicted finding in this examination is that pro-activeness (t-value = 3.787, p-value = 0.000) significantly affects entrepreneurial intention, not just play moderation role (Wong, 2012) but also has a significant impact on EI, according to the results. In addition, pro-activeness alongside the moderating factors collectivism (t-value = 2.628, p-value = 0.009), uncertainty avoidance (t-value = 3.603, p-value = 0.000), masculinity (t-value = 2.602, p-value = 0.010) and long term orientation (t-value = 2.104, p-value = 0.036) additionally have significant effect on entrepreneurial intention, previously not discussed by (Dickel, 2017) in detail and only discussed about environmental performance but we include cultural dimensions as well.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The other predicted finding in this examination is that pro-activeness (t-value = 3.787, p-value = 0.000) significantly affects entrepreneurial intention, not just play moderation role (Wong, 2012) but also has a significant impact on EI, according to the results. In addition, pro-activeness alongside the moderating factors collectivism (t-value = 2.628, p-value = 0.009), uncertainty avoidance (t-value = 3.603, p-value = 0.000), masculinity (t-value = 2.602, p-value = 0.010) and long term orientation (t-value = 2.104, p-value = 0.036) additionally have significant effect on entrepreneurial intention, previously not discussed by (Dickel, 2017) in detail and only discussed about environmental performance but we include cultural dimensions as well.…”
Section: Discussionmentioning
confidence: 57%
“…They interviewed ten Irish women business visionaries and accumulate data about their entrepreneurial encounters. They found that risk do have a place with the gender idea that ought to be International Journal of Human Resource Studies ISSN 2162-3058 2020 enlarged and as per the financial condition (Wong, 2012) investigated about the immediate and aberrant effect of pro-activeness, risk taking and innovativeness on entrepreneurial orientation. Information was gathered from 244 electronics manufacturers in China.…”
Section: Long-term Orientationmentioning
confidence: 99%
“…al., 2012). Some other empirical studies has shown positive impact between product innovation and product positional advantage (Song and Noh, 2006;Wong, 2012;Huang and Tsai, 2014). Such relationship very possibly occurs in religious-based market segment, such as Muslim fashion.…”
Section: Innovativeness and Religio-centric Fashion Advantagementioning
confidence: 90%
“…al., 2013). INN is an organizational culture, values and beliefs to implement innovation (Wong, 2012). Therefore, INN basically is attitude, behaviour, tendency, ability and creativity of an entrepreneur to seek and implement new ideas in order to create something new and unique.…”
Section: Innovativeness and Religio-centric Fashion Advantagementioning
confidence: 99%
“…Technological capability is just one of the most important antecedents of entrepreneurial companies developing new products (Zahra, 1996;Yu et al, 2014). Innovation can negatively impact NPS (Baker & Sinkula, 2005), however this finding may be inverted (Kessler & Bierly, 2002) if the innovation is implemented in order to improve product advantage (Wong, 2012).…”
Section: Technological Capability and Npsmentioning
confidence: 99%